Pengaruh kegunaan, kesesuaian, keuntungan relatif, motivasi hedonic, dan risiko yang dirasakan terhadap penggunaan mobile banking Bank Mandiri Surabaya dimediasi niat perilaku nasabah - Muhammad Zainal Musthofa; Lindiawati Lindiawati (STIE Perbanas Surabaya, 2018)
Mobile banking has been popular as banking service in a couple of years. Many banks in Indonesia have their service, which gets attention from the customers and this make customers use mobile banking service. The study aims to examine the infl uence of perceived usefulness, compatibility, relative advantage, hedonic motivation, and perceived risk on the usage of mobile-banking of Bank Mandiri Surabaya by customer’s behaviour intentions. The data were collected by using questionnaires to 125 responden that use Mandiri mobile-banking. The sample was taken by using a judgement sampling. The hypotheses were analyzed using a partial least square. This research represents to perceived usefulness, compatibility, relative advantage, hedonic motivation and perceived risk. The results shows that perceived usefulness and relative advantage have positive and significant effect, a while compatibility and hedonic motivation have a positive effect but not signifi cant and last perceived risk has a signifi cant and negatif effect on behaviour intentions.